An expert system for forest resources management in Peninsular Malaysia - Mohd. Zukki, Nur Ilyana (2010)
Tropical forests are losing capacity to provide basic goods and services that are essentials to human livelihood due to threatened ecosystems by human activities and climate change. A much finer balance in the allocation of forest land for production, protection, conservation and amenity purposes is necessary for forest continuously play its essential economic, social, cultural and aesthetic roles. Hence, every decision involving forest utilization should consider various criteria that are important for sustainable forest management. Making decision about forest resources management often involves balancing conflicting, inadequate and incompatible values of many users and usage of a resource. One of the most difficult tasks is the effective integration of environmental, economic and social values to achieve ecologically sustainable development. This study integrates an Analytical Hierarchy Process and expert system to assist decision makers to select the best main function of forest resources, forest functional class of a forest area and assist in harvesting decision of non-timber forest product. Based on knowledge acquisition from multiple sources,three levels of hierarchy were developed to select the main forest function of forest area with goal at the highest level, followed by criteria based on Malaysian Criteria and Indicator (2002) as well as alternatives of forest main function at the lowest level. Using this technique, the determination of priority for all the alternatives will be considered. Pairwise comparison matrices are completed by experts using input data for priority ranking of the alternatives. Evaluations of pairwise comparison matrix have to be repeated if the consistency ratios are more than 10% or 0.1. The second and third modules for selecting forest functional class and non-forest timber product harvesting decision respectively are using IF-THEN rules. Verification and validation of FORRM expert system has been done using a case study that is Rotan Tunggal Forest Reserve under management of Forestry Department of Pahang. Sensitivity analyses were conducted to check the impact of change in the input data to the alternatives. The criteria of FORMM expert system evaluation are including user friendliness and system functioning